2010
DOI: 10.1108/02637471011051318
|View full text |Cite
|
Sign up to set email alerts
|

Housing environment preference of young consumers in Guangzhou, China

Abstract: PurposeThe purpose of this paper is to understand the demand pattern and housing preference of young consumers in Guangzhou, China. This study seeks to offer more information for urban planners and housing developers about housing demand from social and cultural perspective.Design/methodology/approachAssisted by a questionnaire survey, a housing environment preference pattern is generated by ranking quality attributes with respect to their relative importance to young consumers. The outcome is analysed by pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 30 publications
(39 reference statements)
6
32
0
2
Order By: Relevance
“…Though housing reform has delinked the connection between work and residence, for many urban Chinese who previously took short commuting for granted, in combination with the low car-ownership rate and imbalanced urban spatial structure, the distance between workplace and residential location is no doubt an important consideration, and proximity between the two would be much favored. Wu et al (2013) and Wu (2009) provide empirical evidence to support this argument. With data from a survey of 3481 households in Beijing in 2009, Wu et al (2013) found that households are more likely to choose to reside in those neighborhoods with high job accessibility and short commuting time.…”
Section: Preference For Short Commutesupporting
confidence: 55%
See 1 more Smart Citation
“…Though housing reform has delinked the connection between work and residence, for many urban Chinese who previously took short commuting for granted, in combination with the low car-ownership rate and imbalanced urban spatial structure, the distance between workplace and residential location is no doubt an important consideration, and proximity between the two would be much favored. Wu et al (2013) and Wu (2009) provide empirical evidence to support this argument. With data from a survey of 3481 households in Beijing in 2009, Wu et al (2013) found that households are more likely to choose to reside in those neighborhoods with high job accessibility and short commuting time.…”
Section: Preference For Short Commutesupporting
confidence: 55%
“…With data from a survey of 3481 households in Beijing in 2009, Wu et al (2013) found that households are more likely to choose to reside in those neighborhoods with high job accessibility and short commuting time. In a study of young housing consumers in Guangzhou, Wu (2009) reveals that proximity to workplace is the second most important determinant of housing choice, after access to a public transport network. Empirical evidence from western cities seems to suggest that accessibility issues such as distance to workplace are not necessarily an important factor influencing people's residential choice (Kim and Morrow-Jones 2005;Morrow-Jones and Kim 2009).…”
Section: Preference For Short Commutementioning
confidence: 99%
“…This explains the popularity of SP data in the housing preference literature. Examples include Bender, Din, Favarger, Hoesli, and Laakso (1997), Bender, Din, Hoesli, and Brocher (2000), Ge and Hokao (2006), Kauko (2006aKauko ( , 2006bKauko ( , 2007, Reed and Mills (2007), Walker and Li (2007), Wang and Li (2004), Wu (2010).…”
Section: Heterogeneity Of Preferences Seldom Addressedmentioning
confidence: 97%
“…Wu conducted a study with the aim of understanding housing demand patterns and preferences of young consumers in Guangzhou, China [4]. In his research, Wu used the "Housing Environment" variable and involved several subvariables such as mobility, community facilities, and community social capital.…”
Section: B Housing Environment Preferencementioning
confidence: 99%
“…This will form the level of property demand that can affect the market price of the property. In Wu's [4] research, the existence of a housing environment preference factor has an influence on price formation. Wu [4] studies Housing Environment Preference by adopting dimensions and indicators which include: Mobility, Community facilities, Community social capital.…”
Section: Introductionmentioning
confidence: 99%